2022
DOI: 10.5098/hmt.19.5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Heat Transfer Characteristics of Corrugated Tube Phase Change Thermal Energy Storage Unit

Abstract: Detailed numerical analysis is presented for heat transfer characteristics of charging or discharging process in phase change thermal energy storage unit with inner corrugated tube. The results indicated that the charging or discharging rate of phase change material (PCM) for the case of inner corrugated tube is obviously higher than that in unit with inner plain tube due to the increasing heat transfer surface. The heat transfer rate increase with the increasing mass flow rate. However, when the mass flow rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Also, eddy blockage gets worst and therefore leading to the degrading the heat transfer process at the top horizontal pipe by 17%. Similar outcomes were acheived related to the heat storage unit with (Ida et al,2022, Kun et al,2022, Hai et al,2019Scott Hai et al,2022, andWenlei et al,2020).…”
Section: Introductionsupporting
confidence: 65%
“…Also, eddy blockage gets worst and therefore leading to the degrading the heat transfer process at the top horizontal pipe by 17%. Similar outcomes were acheived related to the heat storage unit with (Ida et al,2022, Kun et al,2022, Hai et al,2019Scott Hai et al,2022, andWenlei et al,2020).…”
Section: Introductionsupporting
confidence: 65%
“…To reduce the temperature difference between batteries, phase change materials (PCM) are used for battery thermal management because PCM will maintain a small temperature range during phase transition (Mohammed et al, 2022;Zhang et al, 2022). Jilte et al (2021) studied the heat dissipation of batteries with enhanced PCM in different arrangement modes by means of simulation, the results showed that the 7*7*1 arrangement was more efficient than the 7*1*1 arrangement.…”
Section: Introductionmentioning
confidence: 99%